2018
DOI: 10.1002/jez.2180
|View full text |Cite
|
Sign up to set email alerts
|

A potential antiapoptotic regulation: The interaction of heat shock protein 70 and apoptosis‐inducing factor mitochondrial 1 during heat stress and aestivation in sea cucumber

Abstract: The sea cucumber (Apostichopus japonicus) has become a good model organism for studying environmentally induced aestivation in marine invertebrates. A characteristic feature of aestivation in this species is the degeneration of the intestine. In the current study, we hypothesized that energy conservation and cytoprotective strategies need to be coordinated in the intestine to ensure long-term survival during aestivation, and there was potential relationship between heat shock protein 70 (HSP70) and apoptosis-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Based on their widespread existence in various species, from invertebrates to humans [ 18 , 19 , 31 , 32 ], AIFs have been proposed to have an ancient and conserved pyridine nucleotide-disulfide oxidoreductase domain (Pyr_redox domain), which could generate superoxide rather than exhibit antioxidant activity [ 5 ]. Our current study found that Hl AIF-2 contained a Pyr_redox_2 domain and a deduced C-terminal NLS but lacked a recognizable MLS ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their widespread existence in various species, from invertebrates to humans [ 18 , 19 , 31 , 32 ], AIFs have been proposed to have an ancient and conserved pyridine nucleotide-disulfide oxidoreductase domain (Pyr_redox domain), which could generate superoxide rather than exhibit antioxidant activity [ 5 ]. Our current study found that Hl AIF-2 contained a Pyr_redox_2 domain and a deduced C-terminal NLS but lacked a recognizable MLS ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the intestine was the tissue with the highest expression level of AIF mRNA in Pacific white shrimps [ 18 ]. Previous studies showed that HSP70 could inhibit the nuclear translocation of AIFM1 during hibernation and thermal stimulation in A. japonicus , indicating a potential antiapoptotic response in the intestinal cells of sea cucumbers [ 19 ]. On the other hand, AIF-2 is reported to be involved in neural differentiation during embryonic development in vertebrates [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RR420) with the AjCA specific primer pairs (Table 1). β-tubulin (TBB, PIK103) was selected as an internal control and had been previously validated as being unchanged during A. japonicus aestivation in an initial study of reference gene stability [31]. β-actin (ACTB, PIK61412.1) was also selected as another internal control, which was mainly to ensure the constant expression of an internal control and made the results more stable and accurate.…”
Section: Methodsmentioning
confidence: 99%
“…The aestivating A. japonicus is marked with intestinal atrophy along with alteration of microbiota and impairment of intestinal mucosa integrity. These changes will exaggerate the functions of TLR signalling pathways in intestinal inflammation and apoptosis (Wang, Li, Chen, Storey, & Wang, ). Arousal process is similar to the regeneration of intestine combined with the recovery of function and normal metabolism (Su et al, ; Sun, Yang, Chen, Ma, & Lin, ).…”
Section: Primers Used For Tlr Signalling Pathway Expression Analysismentioning
confidence: 99%